(untitled) (Journal of the College of Basic Education, 2022)
The problems associated with using the land for the purposes of transportation in all cases that the urban community does not want about this use, especially that the goal of man and his purposes related to transportation is not only to reach his goals, but he seeks to achieve safety and comfort and shorten the time and cost and enjoyment in traveling as well.These problems result from the relationship between technological variables and their development on the one hand, and land use patterns on the other hand. If movement occurs between residential areas and commercial areas, as facilitating the movement of people (traffic) has become more difficult with the expansion of the city, and this problem is linked to the factor of the inherited parts that were established and planned